Real Time Extraction and Processing of Social Tweets - Bandgar, BM; Kumar, Binod (International Journal of Computer Sciences and Engineering, 2015)
Twitter has become one of the most popular micro-blogging platforms recently. Millions of users can share their thoughts and opinions about different aspects and events on the micro-blogging platform. Therefore, Twitter is considered as a rich source of information for decision making and sentiment analysis. Obtaining the real time tweets on the particular topic is one of the challenging tasks. There are numbers of related publications, but which have limitations; also their methods are not much clear and mostly based on Linux based system and uses integrated tools, which is most complex job. Therefore, in this research paper we develop the indigenous Windows based user friendly application in Java to extract, process and classify the real time social network tweet. The tweets are processed for removal of hash, tags and URL and removed the stop words from sentence and tried to detect, analyze the abbreviations or slangs. The meaningful real time tweets are obtained and used for sentimental analysis.